ANALISIS PENGETAHUAN GIZI DAN HIDRASI TERHADAP SIKAP DAN PERILAKU IBU DI MASA KEHAMILAN - Mulyani, Erry Yudhya; Jus’at, Idrus; Angkasa, Dudung; Anggiruling, Dwikani Oklita (GIZI INDONESIA, 2019)
Nutrition and health behavior during pregnancy has an impact on fetal health and outcome birth.The aims of this study were to analyze the relationship between nutrition and hydration knowledge on maternal attitudes and behavior during pregnancy.This study was a cross-sectional study, conducted in Kebon Jeruk District Health Center, West Jakarta.The research subjects were pregnant women in the second and third trimesters who examined their pregnancies at the study site, totaling 100 subjects. The data collected were characteristics subjects, anthropometrics, level of knowledges, attitudes, and behaviors. Data was taken through interviews and anthropometric measurements by enumerators and health professional trainee. Pearson's correlation and chi-square tests were used to analyze data.Subjects were on average 29.0 ± 5.7 years, body weight 54.3 ± 8.6 kg, body height 153.7 ± 5.4 cm, body mass index 23.0 ± 3.8 kg/m2, upper arm circumference 26.4 ± 3.3 cm, and hemoglobin level 11.9 ± 0.9 g/dL. There was a positive relationship between nutrition and hydration knowledge on the behavior of pregnant women (p0.05).The proportion of mothers in the high-level group had a positive attitude about water consumption when nausea and vomiting were more than those with low-level group (p0.05).Mothers with a high-level group of knowledge have a tendency to have frequent water consumption and vary in diet from the low-level group (p 0.05).Therefore, the health professional needs to give the nutrition education which reliable and accurate to pregnant women in antenatal care.